ENVIRONMENTAL IMPACT OF SOCIO-ECONOMIC ACTIVITIES ON THE WATER QUALITY OF CUA BE, NHA TRANG - Vinh, Le Thi; Kiem, Duong Trong; Thu, Nguyen Hong; Tam, Pham Huu; Ngoc, Pham Hong (Vietnam Journal of Marine Science and Technology, 2008)
The waters in Cua Be plays an important role to the port’s activities and aquaculture. Impact assessment ofhuman activities on wanter quality (2007) indicated that this waters received high amounts of waste water from different activities around. The waste water from domestic and seafood processing contained high values of total suspended solids, nutrients, organic matters, coliform density and BOD5. Waste water from aquaculture also provided nutrients for this waters. Fishing boat’s activilies discharged hydrocarbon while aclivities of dredging the river bed and encroachment on the sea discharged suspended solids on this waters. Therefore, eutrophication occurred in this waters with comparatively high nutrient concentrations (maximum of NH3,4: 242 μgN/l, NO2: 67 μgN/l, NO3: 508 μgN/l, organic N: 3151 μgN/l. PO4: 1550 μgP/l, organic P: 920 μgN/l), high coliform density (maximum of 240000 MPN/100 ml), high BOD5 value (maximum: 13.2 mg/1) and low DO (sometimes DO < 5 mg/1). This waters was also conlarninated by hydrocarbon (maximum: 1200 μg/l) and total suspended solids (maximum: 75.4 mg/1).